Oxidative Stress and Renal Fibrosis: Recent Insights for the Development of Novel Therapeutic Strategies - Lv, Wenshan; Booz, George W.; Fan, Fan; Wang, Yangang; Roman, Richard J. (Frontiers in Physiology, 2018)
Chronic kidney disease (CKD) is a significant worldwide healthcare problem. Regardless of the initial injury, renal fibrosis is the common final pathway leading to end stage renal disease. Although the underlying mechanisms are not fully defined, evidence indicates that besides inflammation, oxidative stress plays a crucial role in the etiology of renal fibrosis. Oxidative stress results from an imbalance between the production of free radicals that are often increased by inflammation and mitochondrial dysfunction, and reduced anti-oxidant defenses. Several studies have demonstrated that oxidative stress may occur secondary to activation of transforming growth factor β1 (TGF-β1) activity, consistent with its role to increase nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (Nox) activity. A number of other oxidative stress-related signal pathways have also been identified, such as nuclear factor erythroid-2 related factor 2 (Nrf2), the nitric oxide (NO)-cyclic guanosine monophosphate (cGMP)-cGMP-dependent protein kinase 1-phosphodiesterase (cGMP-cGK1-PDE) signaling pathway, and the peroxisome proliferator-activated receptor gamma (PPARγ) pathway. Several antioxidant and renoprotective agents, including cysteamine bitartrate, epoxyeicosatrienoic acids (EETs), and cytoglobin (Cygb) have demonstrated ameliorative effects on renal fibrosis in preclinical or clinical studies. The mechanism of action of many traditional Chinese medicines used to treat renal disorders is based on their antioxidant properties, which could form the basis for new therapeutic approaches. This review focuses on the signaling pathways triggered by oxidative stress that lead to renal fibrosis and provides an update on the development of novel anti-oxidant therapies for CKD.